2016
DOI: 10.3233/jad-160176
|View full text |Cite
|
Sign up to set email alerts
|

Association between Cerebrospinal Fluid Biomarkers for Alzheimer’s Disease, APOE Genotypes and Auditory Verbal Learning Task in Subjective Cognitive Decline, Mild Cognitive Impairment, and Alzheimer’s Disease

Abstract: In the course of Alzheimer's disease (AD), early pathological changes in the brain start decades before any clinical manifestation. The concentration levels of AD cerebrospinal fluid (CSF) biomarkers, such as amyloid-β1-42 (Aβ1-42), total tau (T-tau), and phosphorylated tau (P-tau), may reflect a cerebral pathology facilitating an early diagnosis of the disease and predicting a cognitive deterioration. The aim of this study was to estimate the prevalence of AD CSF biomarkers in those individuals with a subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…For detection of p-tau, the INNOTEST ® PHOSPHO-TAU(181P) was used. Cut off values of assayed CSF markers for AD diagnosis were Aβ42 < 609.54 pg/ml, t-tau > 277.02 pg/ml and p-tau > 55.08 pg/ml, as described previously in [88]. Patients’ characteristics are presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…For detection of p-tau, the INNOTEST ® PHOSPHO-TAU(181P) was used. Cut off values of assayed CSF markers for AD diagnosis were Aβ42 < 609.54 pg/ml, t-tau > 277.02 pg/ml and p-tau > 55.08 pg/ml, as described previously in [88]. Patients’ characteristics are presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…SILK studies have shown that the A␤ 42 :A␤ 40 turnover rate positively correlates with amyloid plaque load and demonstrate that understanding A␤ dynamics in different compartments including CSF, blood, and brain tissue is crucial to improving therapy. Thus, studies showing significantly lower levels of CSF A␤ 42 in AD patients with more severe cognitive impairment [65] are unable to provide information on changes in A␤ turnover occurring either during the circadian cycle or during the progression of disease.…”
Section: Circadian Rhythmmentioning
confidence: 99%
“…The study population was divided into two subgroups: subgroup 1: non-converters, who did not convert to AD (31 patients) and subgroup 2: converters, who converted to AD (9 patients). The characteristics of subgroups, including the results of CSF are shown in Table I, together with the cut-off points (established in our laboratory, described in our previous study [8]). …”
Section: Resultsmentioning
confidence: 99%